Tinjauan Kriminologi terhadap Korban Tindak Pidana Anak Disabilitas - Maria Ferba Editya; Rayani Saragih (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the factors that cause criminal acts against children with disabilities, to determine the implementation of legal protection for children with disabilities. This type of research method is normative legal research or commonly called normative juridical research. Techniques Data collection is carried out in several stages, such as literature study assistance. The literature study was carried out in compiling the background of the problem, literature review, framework of thought by collecting initial data and information from books that discussed the Criminology Review of Victims of Criminal Acts of Children with Disabilities. Law Number 8 of 2016 Article 76e concerning Persons with Disabilities explains that every person is prohibited from committing violence or threats of violence, coercing, deceiving, committing a series of lies, or persuading a child to commit or allow obscene acts to be carried out, if these acts are committed, then in accordance with Article 82 paragraph (1) will be threatened with a maximum imprisonment of 5 (five) years in prison and a fine of 5 million.